The mediating effects of psychological capital and career success in the relationship between leadership styles and job satisfaction among nurse managers: a cross-sectional study - Panpan Cui; Shuying Chang; Gang Tian; Zhen Li; Chunyan Cheng; Lu Chang; Junmei Zhang; Hongmei Zhang; Hengyu Hu (BMC Nursing)
Abstract Background Nursing managers’ leadership styles significantly influence their job satisfaction, yet the underlying mechanisms remain unclear. This study explores the mediating roles of psychological capital and career success in the relationship between leadership styles—transformational (TFL), transactional (TSL), and passive/avoidant (PAL)—and job satisfaction (JS). Methods A cross-sectional study was conducted in May 2024 with nurse managers from 20 hospitals in Henan Province, China. Of 810 contacted, 784 participated. Participants completed validated instruments, including the Multifactor Leadership Questionnaire, Psychological Capital Scale, Career Success Scale, and Minnesota Satisfaction Questionnaire. Pearson’s correlation and serial mediation analyses were performed using IBM SPSS (version 21) and the PROCESS macro (version 3.4). Results Both TFL and TSL had direct and positive effects on JS, with psychological capital and career success serving as partial mediators. Significant sequential mediation effects were found for both styles—for example, TFL→ psychological capital → career success →JS (β = 0.112, 95% CI [0.073, 0.155]) and TSL→ psychological capital → career success →JS (β = 0.260, 95% CI [0.188, 0.339]). In contrast, PAL showed no significant direct or total indirect effect on JS, though the sequential mediation pathway via psychological capital and career success was significant (β =–0.077, 95% CI [–0.122, –0.035]). Conclusion This study demonstrates that both TFL and TSL significantly influence nurse managers’ job satisfaction, not only through direct effects but also indirectly via psychological capital and career success, including their sequential mediation. These findings highlight the critical role of leadership in enhancing psychological resources and career development. Strengthening effective leadership styles may serve as a strategic pathway to fostering a more supportive work environment and improving job satisfaction in healthcare settings.